EARLY DETECTION OF HYPERCHOLESTEROLEMIA IN THE ELDERLY - Debie Anggraini; Dita Hasni (Jurnal Abdimas Saintika, 2021)
Hypercholesterolemia is total cholesterol inblood with high cholesterol levels that is 200 mg/dl. Hypercholesterolemia is one of the indicators of atherosclerosis in blood vessels and become a top priority in overcoming health problems in developed and developing countries. The cause of hypercholesterolemia is the intake of unhealthy food, such as overeating fat, low consumption of fruits and vegetables, obesity, low physical activity, hypertension, stress, smoking and alcohol use.